Determinants Distribution of Financing and the Implications to Profitability: Empirical Study on Cooperative Sharia Baitul Maal wa Tamwil (BMT) in Indonesia - Oyong Lisa (Emerald Publishing Limited, 2016)
Financing is one of the main activities and a major source of revenue for Islamic Cooperatives. This study aimed to analyze the effect of capital structure, third party funds and non-performing financing to the finance portfolio as well as to analyze the effect of capital structure, deposits, non-performing financing and the distribution of funding to profitability. The analysis technique used is multiple regression analysis, using F test and t test. The results of the analysis showed that the capital structure, third party funds and non-performing financing significantly effect on the distribution of funding. Capital structure, third party funds, and the distribution of funding has a significant effect on profitability, Sharia Cooperative BMT in Indonesia. While non-performing financing does not affect the profitability of Islamic Cooperative Baitul Maal Tamwil in Indonesia.